A Review on Tribological, Mechanical, Corrosion and Wear Characteristics of Stir Cast AA6061 Composites. (2020) - Raja, S.; Ravichandran, M.; Stalin, B.; Anandakrishnan, V.
Abstract: AA6061 composites is the most interesting engineering material that have the ability of fulfilling the demands of recent engineering applications used in sectors like automobile, defence, aerospace and marine industries. This demand is due to reducing production cost, improved mechanical properties, formability and easier production technique. Selecting the exact blend of reinforcing materials is most important factor for the performance of the material. This is due to the process parameters related with the reinforcing particulates. In this paper efforts are made to review diverse blend of reinforcing materials used in the production of stir casted AA6061 composites and what way it affects the tribological, mechanical, corrosion and wear performance of the materials. The key research areas for further improvement on AA6061 hybrid composites are also suggested